Effects of suction on steady boundary layer stagnation-point flow and heat transfer in porous medium towards a stretching/shrinking sheet with thermal radiation - Kaharuddin, N.A.H.; Rosali, H.; Rahmin, N.A. (Lviv Polytechnic National University, 2025)
In this study, the effects of suction and thermal radiation on steady boundary layer stagnation point flow and heat transfer in porous medium towards a stretching and shrinking sheet is investigated. The governing partial differential equations (PDEs) are transformed into Nonlinear Ordinary Differential Equations (ODEs) utilizing similarity transformation. These equations are then solved numerically using the function BVP4C in MATLAB, with the numerical results presented through graphical illustrations. The investigation uncovers the existence of dual solutions and unique solutions within specific ranges of velocity ratio parameter ε, depending on the parameters involved. Furthermore, it is found that both the skin friction coefficient and the local Nusselt number increase as suction S and permeability parameter K increase. Also, higher values of Prandtl number Pr and thermal radiation parameter R result in a thinner thermal boundary layer.